Perlindungan Hukum Transaksi Elektronik Bagi Pengguna Internet Ditinjau Dari UU Perlindungan Konsumen No 8 Tahun 19999 - Kukuh Cahyono (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2020)
This study examines the legal protection of consumers in making transactions through online methods in terms of the Consumer Protection Law Number 8 of 1999. In online transactions it has a very typical character where transactions are Internet so that there is no meeting between the seller and the buyer ( consumers) but only through these social media. On the one hand, it looks very beneficial for consumers because consumers can directly choose the desired item with a wide variety of choices, both in price, type and quality. However, on the other hand, violations are very risky to consumers, which will harm consumers. Therefore, the authors see the need for legal protection for consumers who transact via the internet, so that the conclusion is with the existence of Law No. 8 of 1999 so that consumers will be more awake in making transactions through online media.